Pre-selection of Globular Clusters for Detecting Intermediate-Mass Black Holes via Microlensing - Fatimah Zahra; Anton Timur Jaelani (Spektra: Jurnal Fisika dan Aplikasinya, 2026)
Intermediate-mass black holes (IMBHs) are the key to understanding the formation of supermassive black holes (SMBHs) that are typically found in centers of massive galaxies. In general definition, IMBHs are black holes masses ranging from 102 M⨀ to 105 M⨀. Black hole seeding theory suggests that IMBHs formed at high redshifts (z ≥ 0) through gravitational collapse of Population III stars, direct collapse of protogalaxy clouds, or stellar collisions inside high-density clusters. These IMBHs evolve into SMBHs through accretion and mergers. However, not all of these IMBHs are successful in forming SMBHs. Those that fail are hypothesized to be observable in the local universe, particularly in globular clusters and dwarf galaxies. IMBHs have yet to be definitively detected, however several strong candidates have been located in the cores of globular clusters. This study describes the preliminary selection stage of globular cluster candidates with the aim to look further into the possibility of detecting IMBHs via microlensing. The selection process was based on several physical properties of the globular clusters including mass, metallicity, and central velocity dispersion. Since background star density strongly affects microlensing detection probability, we restricted the sample to clusters located in the direction of the Galactic center. We utilized Gaia DR3 data to estimate background star density for selected globular clusters using proper motion filtering and Theil-Sen regression method. These estimates provide the foundation for further subsequent simulations of microlensing detection probabilities associated with central IMBHs.